2008
DOI: 10.1021/es702969f
|View full text |Cite
|
Sign up to set email alerts
|

Food-Miles and the Relative Climate Impacts of Food Choices in the United States

Abstract: Despite significant recent public concern and media attention to the environmental impacts of food, few studies in the United States have systematically compared the life-cycle greenhouse gas (GHG) emissions associated with food production against long-distance distribution, aka "food-miles." We find that although food is transported long distances in general (1640 km delivery and 6760 km life-cycle supply chain on average) the GHG emissions associated with food are dominated by the production phase, contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
548
2
11

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 862 publications
(604 citation statements)
references
References 23 publications
15
548
2
11
Order By: Relevance
“…The consumption of local food in an average American household yields a maximum reduction of 4-5% of the total greenhouse gas emissions related to food consumption. For fruits and vegetables this share is 11%, because the production phase is less emission intensive (Weber and Matthews 2008). For the UK, a recent life-cycle analysis of community agriculture on vacant land reported a reduction of only 0.4% of the total food-related emissions (Kulak et al 2013).…”
Section: Global Climate Regulating Servicesmentioning
confidence: 99%
“…The consumption of local food in an average American household yields a maximum reduction of 4-5% of the total greenhouse gas emissions related to food consumption. For fruits and vegetables this share is 11%, because the production phase is less emission intensive (Weber and Matthews 2008). For the UK, a recent life-cycle analysis of community agriculture on vacant land reported a reduction of only 0.4% of the total food-related emissions (Kulak et al 2013).…”
Section: Global Climate Regulating Servicesmentioning
confidence: 99%
“…Weber & Matthews (2008) found red meat is on average three times more carbon intense than fish and poultry. For this reason, the food literature on climate change focuses on cows and feedstock such as soy.…”
Section: Food Footprintsmentioning
confidence: 99%
“…A robust meta-study by Weber & Matthews (2008) found that most food-related carbon emissions occur during production (83%). Garnett (2009) argues that LCAs are insufficient for food because they fail to capture the more complex land-use interactions that occur worldwide, particularly with livestock food consumption, deforestation, and feeder crops.…”
Section: Food Footprintsmentioning
confidence: 99%
See 2 more Smart Citations